Programa de escola de coluna : estratégia de promoção da saúde - Trindade, Ana Paula Nassif Tondato da (2020)
Introduction: More than a third of the Brazilian population believes that chronic pain compromises their usual activities, and more than three quarters consider chronic pain to be limiting for recreational activities, social and family relationships. Due to its structure, the “Back School” program can be considered an efficient strategy for health promotion, prevention and rehabilitation. Objectives: Carry out physiotherapeutic intervention in patients with back pain, using the strategy recommended by the Back School and implement the Back School Program in the municipality, as a Health Promotion strategy. Methodology: This is a prospective and longitudinal interventional research. quantitative. The inclusion criteria were: participants who were on the waiting list for care in the public network, aged over 18 years, presenting pain in any region of the spine, having medical referral and who were willing to participate in the project for 3 months. Classes were formed to receive assistance as a group of 3 or 4 people. In the initial evaluation, there was a physiotherapeutic evaluation, followed by the application of the Short-Form Quality of Life Questionnaire SF-36, then the Oswestry Disability Index (ODI) questionnaire and finally the Nordic Musculoskeletal Questionnaire (QNSO). In the reassessment, the participants answered the same initial questionnaires again. Results: 81 participants answered the questionnaires completely before and after the evaluation. The Back School program was implemented as a pilot project based on this study. A total of 4,996 calls were made. The participants were 49.7 ± 12.34 years old, most of them female (80.2%). When analyzing the domains of the SF-36 questionnaire, we obtained improvement in all domains, not being significant only in the domains of General Health, Social Aspect and Mental Health. The average obtained with the ODI was 16.65 ± 8.08 before the intervention and 11.63 ± 7.89 after the intervention, showing a significant difference. Regarding the results obtained by the QNSO questionnaire in the last 12 months after the intervention, all participants reported improvement. With regard to the last seven days, the wrist, hand and fingers regions and the ankle and feet regions were the only ones that showed a slight increase. Final considerations: 12 months after the beginning of the program, the results presented indicated that there was an improvement in the clinical condition of the participants, as well as a reduction in the waiting time for the beginning of treatment. In view of the positive results presented, the Department of Health proposed to the Municipal Government to renew the program, which happened after a new bidding process carried out to hire new professionals. Keywords: Spinal Diseases. Quality of life. Unified Health System. Occupational Health.